PERAN UNITED NATIONS PROGRAMME ON HIV AND AIDS (UNAIDS) DALAM MENEKAN PREVALANSI HUMAN IMMUNODEFICIENCY VIRUS (HIV) DAN ACQUIRED IMMUNE DEFICIENCY SYNDROME (AIDS) PADA KELOMPOK KUNCI DI THAILAND TAHUN 2018-2021 - Salwa Ananda Atikah; Saiman Pakpahan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
This study discusses the role of UNAIDS in suppressing the spread of HIV and AIDS in Thailand. HIV and AIDS are viruses that threaten the immune system and can cause death. HIV and AIDS has been declared a global epidemic by WHO. Thailand is one of the countries in Southeast Asia with the highest HIV prevalence rate in Southeast Asia. The HIV epidemic in Thailand has ended, but HIV prevalence in key groups is still very high. This is what makes UNAIDS help Thailand with the programs it has made through the PCB (Program Coordinating Board). This study uses a qualitative method, with data collection techniques through library research which originates from a number of literature related to the problem under study. This research uses the perspective of Pluralism and International Organization theory. The results of this paper found that UNAIDS cooperated with several UN international organizations, the Thai government, Thai NGOs. UNAIDS became an instrument by helping Thailand achieve the 95-95-95 fast-track program and the Joint Program On AIDS With Key Populations. There are several efforts to suppress HIV in the Joint Program, namely providing PreP treatment to young people, upholding human rights and gender equality, and assisting with program funding. The role of UNAIDS as an Arena is to hold national and international meetings with stakeholders in Thailand and policy advocacy. The role of UNAIDS as an actor is by forming a Zero Discrimination campaign and collaborating with the Global Fund Keywords: HIV, AIDS, UNAIDS, Key Population, Thailand.